The Effect of Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), Net Interest Margin (NIM), Loan to Deposit Ratio (LDR) and Operational Costs and Operational Revenue (BOPO) On Return on Assets (ROA) in Bank IV Indonesia - Muhammad Budi Rifansa; Nur Aisyah F. Pulungan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze the effect of capital adequacy ratio (CAR), non-performing loan (NPL), net interest margin (NIM), loan to deposit ratio (LDR) and operating costs of operating income (BOPO) on return on assets (ROA) in book banks. IV in Indonesia. The population in this study is book IV bank listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. Research data is secondary data with 5 years of observation. The method of determining the sample using purposive sampling, where from all book IV banks listed on the IDX, 10 book IV banks that reported their financial statements during the study period were taken. The data analysis method used is panel data regression Random Effect Model. The results of this study can be concluded that Return On Assets can be explained or influenced by the variables of capital adequacy ratio (CAR), non-performing loan (NPL), net interest margin (NIM), loan to deposit ratio (LDR), operating costs of operating income (BOPO). ) of 96.62%, while the remaining 3.38% is influenced by other variables outside the model. The results showed that the ratio of CAR, NPL and BOPO had no effect and the ratio of NIM and LDR had a positive and significant effect on Return On Assets (ROA).